Broiler Industry 2022
DOI: 10.5772/intechopen.101894
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Manipulation: Embryonic Development, Hatchability, and Hatching Quality of Broiler Chicks

Abstract: Here, PRISMA guidelines were utilized to systematically evaluate the publications reporting the effect of thermal manipulation during embryogenesis on incubation performance, hatchability, and hatching quality of broiler chicks. The search and selection of eligible publications was through databases web of science, PubMed, and Scopus. Publications written in English between 2015 and September 2021 were considered. It is evidenced that during TM, key considerations include duration and strength of TM besides st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Since then, this method used in different avian species have shown that a change in temperature during the critical period of embryogenesis can result in various phenotypes during the later life of the animal, known as a programming indicator. In chicken, the timing, the duration and the intensity of the thermal manipulation had to be accurately chosen according to the purpose of the programming and to avoid deleterious effects ( Piestun et al, 2009 ; Loyau et al, 2015 ; Al-Rukibat et al, 2016 ; Tainika, 2022 ). This concept of embryonic thermal programming has been used in broiler field to improve their thermoregulation and resistance to heat shock during the rearing period ( Yahav and McMurtry, 2001 ; Loyau et al, 2015 ; Tainika, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, this method used in different avian species have shown that a change in temperature during the critical period of embryogenesis can result in various phenotypes during the later life of the animal, known as a programming indicator. In chicken, the timing, the duration and the intensity of the thermal manipulation had to be accurately chosen according to the purpose of the programming and to avoid deleterious effects ( Piestun et al, 2009 ; Loyau et al, 2015 ; Al-Rukibat et al, 2016 ; Tainika, 2022 ). This concept of embryonic thermal programming has been used in broiler field to improve their thermoregulation and resistance to heat shock during the rearing period ( Yahav and McMurtry, 2001 ; Loyau et al, 2015 ; Tainika, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In chicken, the timing, the duration and the intensity of the thermal manipulation had to be accurately chosen according to the purpose of the programming and to avoid deleterious effects ( Piestun et al, 2009 ; Loyau et al, 2015 ; Al-Rukibat et al, 2016 ; Tainika, 2022 ). This concept of embryonic thermal programming has been used in broiler field to improve their thermoregulation and resistance to heat shock during the rearing period ( Yahav and McMurtry, 2001 ; Loyau et al, 2015 ; Tainika, 2022 ). It was also shown that this type of programming could improve other performances such as meat production in broiler ( Piestun et al, 2011 ) or more recently foie gras production in mule duck.…”
Section: Introductionmentioning
confidence: 99%